The perception of lexical stress in Malaysian English - Ernie Adnan,; Stefanie Pillai,; Chiew, Poh Shin (Penerbit Universiti Kebangsaan Malaysia, 2020)
Malaysian English is described as a variety of English that lacks perceivable lexical stress. This, in turn, could affect its intelligibility to non-Malaysian listeners. This paper examines if lexical stress can be detected in Malaysian English. The findings were based on two listening tasks completed by 65 respondents from three neighbouring countries: Indonesia, Thailand, and the Philippines. In the first task, they were required to listen to recordings of the Malaysian speakers, and mark the stressed syllables in the test words. In the second task, they wrote out the words they heard in the recordings. The findings indicate that most of the respondents were generally able to identify the stressed syllables in the test words. However, the more syllables a word had, the more difficult it was to identify the stressed syllable. Context was also an important factor as the listeners found it easier to identify, and make out the test words when they were placed in a sentence. Speakers who used less English in their daily interactions, and who declared a lower level of English proficiency had more difficulty identifying the stressed syllables, and making out the words being uttered by the Malaysian English speakers.